Articles
Register
Sign In
Search
TheOasisSkaaf
@TheOasisSkaaf
April 2019
2
8
Report
Supprimer les parenthèses dans les expression suivantes et reduir le resultas urangent svp svp 15 ptn
C=6+(7x-6)-(1+7x)-1
D=-2+(5-y)+(-3+6y)
Please enter comments
Please enter your name.
Please enter the correct email address.
Agree to
terms and service
You must agree before submitting.
Send
Lista de comentários
maudmarine
Verified answer
C=6+(7x-6)-(1+7x)-1
C = 6 + 7x - 6 - 1 - 7x - 1
C = 7 - 7x + 6 - 6 - 1
C = - 1
D=-2+(5-y)+(-3+6y)
D = - 2 + 5 - y - 3 + 6y
D = - y + 6y - 2 - 3 + 5
D = 5y
0 votes
Thanks 0
nonoduchablais
Salut !
J'espère t'avoir aidé(e) ! :)
0 votes
Thanks 0
More Questions From This User
See All
TheOasisSkaaf
April 2019 | 0 Respostas
Responda
×
Report "Supprimer les parenthèses dans les expression suivantes et reduir le resultas urangent svp svp 15 pt.... Pergunta de ideia de TheOasisSkaaf"
Your name
Email
Reason
-Select Reason-
Pornographic
Defamatory
Illegal/Unlawful
Spam
Other Terms Of Service Violation
File a copyright complaint
Description
Helpful Links
Sobre nós
Política de Privacidade
Termos e Condições
direito autoral
Contate-Nos
Helpful Social
Get monthly updates
Submit
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Verified answer
C=6+(7x-6)-(1+7x)-1C = 6 + 7x - 6 - 1 - 7x - 1
C = 7 - 7x + 6 - 6 - 1
C = - 1
D=-2+(5-y)+(-3+6y)
D = - 2 + 5 - y - 3 + 6y
D = - y + 6y - 2 - 3 + 5
D = 5y
J'espère t'avoir aidé(e) ! :)